2021
DOI: 10.1080/19476337.2021.1946158
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced glucosamine production from Aspergillus oryzae NCH-42 via acidic stress under submerged fermentation

Abstract: Glucosamine (GlcN) has been widely used to treat osteoarthritis. However, GlcN derived from crustacean shells has several drawbacks, and it is not vegan-friendly. Here, we produced GlcN from the biomass of Aspergillus oryzae NCH-42 and investigated the effects of environmental factors (e.g. carbon and nitrogen sources, temperature, and pH) on the GlcN production of the fungal biomass. The acidic stress resulted in significantly higher GlcN content in the cell wall of A. oryzae NCH-42. Moreover, the SEM examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, manipulating the temperature and other environmental factors modulates the transcriptional expression of AoErg19 to regulate the biosynthesis of corresponding secondary metabolites. The yield of A. oryzae NCH-42 was low at 20 • C, while the yields of GlcN were high at 25 • C and 30 • C [93]. Additionally, a study using A. oryzae to produce fructo-oligosaccharides revealed that the enhanced activity of mutant V242E is not affected by reaction temperature or other environmental factors [107].…”
Section: The Impact Of Temperaturementioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, manipulating the temperature and other environmental factors modulates the transcriptional expression of AoErg19 to regulate the biosynthesis of corresponding secondary metabolites. The yield of A. oryzae NCH-42 was low at 20 • C, while the yields of GlcN were high at 25 • C and 30 • C [93]. Additionally, a study using A. oryzae to produce fructo-oligosaccharides revealed that the enhanced activity of mutant V242E is not affected by reaction temperature or other environmental factors [107].…”
Section: The Impact Of Temperaturementioning
confidence: 97%
“…The pH also influences GlcN yield. At pH 2.5, A. oryzae NCH-42 produces the highest GlcN yield, with GlcN concentration and content being 4.1 and 2.4 times higher than those at pH 4~7, respectively [93]. However, excessive acidity (pH 2.0) significantly reduces the GlcN yield of A. oryzae NCH-42, making it inefficient under acidic conditions.…”
Section: The Impact Of Other Factorsmentioning
confidence: 98%
See 1 more Smart Citation